Student Recruitment Strategies of an Indonesian Private University Website: A Multimodal Social Semiotic - Mia Rosliana; Piqni Patimah; Hilda Nursyifa (Siliwangi University, 2021)
Recently, empirical investigation focusing on website analysis remains burgeoning. Conversely, research accentuating student recruitment strategies in websites is still under-researched, particularly in Indonesian private university websites. To fill this gap, this study aimed to scrutinize how a private university employed recruitment strategies through its website viewed from a multimodal perspective. The corpus of this study was a homepage website of the private university. It was collected through document analysis and analyzed with Multimodal Social Semiotics (MSS) (Kress, 2010). The findings reported that the university website provides an attractive appearance on its website, so it can attract the attention of its website visitors. Briefly, this study offers valuable insights to conceptualize, design and inform audiences from a multimodal perspective.